PENGARUH STABILITAS KEUANGAN, KETIDAKEFEKTIFAN PENGAWASAN, DAN PERGANTIAN KAP TERHADAP KECURANGAN LAPORAN KEUANGAN : PERAN MODERASI KEPEMILIKAN INSTITUSIONAL - Retno Wulandari (2021)
This research aims to examine the effect of pressure proxied by financial stability, opportunities proxied by ineffective supervision, and rationalization proxied by voluntary KAP turnover on the practice of fraudulent financial statements. The population that is the object of research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) conducted in the 2017- 2020 period, totaling 195. The determination of the sample is carried out by purposive sampling technique with a total of 128 samples. This research applies quantitative analysis techniques as an analytical method. Hypothesis testing in this research uses Panel Data Regression Analysis with a significance level of 5 percent and the F-score model as a measurement of the dependent variable. The results obtained in this test are: 1) Financial stability has a significant positive effect on financial statement fraud 2) Ineffective supervision and KAP switching have no significant effect on financial statement fraud 3) Institutional ownership is able to moderate the stability relationship financial statements and fraudulent financial statements 3) Institutional ownership is not able to moderate the relationship between ineffective supervision and KAP turnover on financial statement fraud